Village matters: relocating villages in the contemporary anthropology of India - Mines, Diane P.; Yazgi, Nicolas (Oxford Univ. Press, 2010)
Papers presented at the 18th European Conference on Modern South Asian Studies, held at Lund on 7th July 2004